The Irishman : Frank Sheeran and closing the case on Jimmy Hoffa - Brandt, Charles (Steerforth Press, 2019)
The Irishman is an epic saga of organized crime in post-war America told through the eyes of World War II veteran Frank Sheeran, a hustler and hitman who worked for legendary crime boss Russell Bufalino alongside some of the most notorious figures of the 20th Century. Spanning decades, Sheeran's story chronicles one of the greatest unsolved mysteries in American history, the disappearance of legendary union boss Jimmy Hoffa, and it offers a monumental journey through the hidden corridors of organized crime: its inner workings, rivalries and connections to mainstream politics. Sheeran would rise to a position of such prominence that in a RICO suit against The Commission of La Cosa Nostra, the US Government would name him as one of only two non-Italians in conspiracy with the Commission. Sheeran is listed alongside the likes of Anthony "Tony Pro" Provenzano and Anthony "Fat Tony" Salerno. In the course of nearly five years of recorded interviews, Sheeran confessed to Charles Brandt that he handled more than twenty-five hits for the mob, and Brandt turned Sheeran's story into a page-turning true crime classic. --Amazon.com.